SMAD7 controls iron metabolism as a potent inhibitor of hepcidin expression - Mleczko-Sanecka, Katarzyna; Casanovas, Guillem; Ragab, Anan; Breitkopf-Heinlein, Katja; Müller, Alexandra; Boutros, Michael; Dooley, Steven; Hentze, Matthias W.; Muckenthaler, Martina (Blood, 2010)
Hepcidin is the master regulatory hormone of systemic iron metabolism. Hepcidin deficiency causes common iron overload syndromes whereas its overexpression is responsible for microcytic anemias. Hepcidin transcription is activated by the bone morphogenetic protein (BMP) and the inflammatory JAK-STAT pathways, whereas comparatively little is known about how hepcidin expression is inhibited. By using high-throughput siRNA screening we identified SMAD7 as a potent hepcidin suppressor. SMAD7 is an inhibitory SMAD protein that mediates a negative feedback loop to both transforming growth factor-β and BMP signaling and that recently was shown to be coregulated with hepcidin via SMAD4 in response to altered iron availability in vivo. We show that SMAD7 is coregulated with hepcidin by BMPs in primary murine hepatocytes and that SMAD7 overexpression completely abolishes hepcidin activation by BMPs and transforming growth factor-β. We identify a distinct SMAD regulatory motif (GTCAAGAC) within the hepcidin promoter involved in SMAD7-dependent hepcidin suppression, demonstrating that SMAD7 does not simply antagonize the previously reported hemojuvelin/BMP-responsive elements. This work identifies a potent inhibitory factor for hepcidin expression and uncovers a negative feedback pathway for hepcidin regulation, providing insight into a mechanism how hepcidin expression may be limited to avoid iron deficiency.